2003
DOI: 10.1115/1.1561812
|View full text |Cite
|
Sign up to set email alerts
|

Combustor Turbine Interface Studies—Part 2: Flow and Thermal Field Measurements

Abstract: Most turbine inlet flows resulting from the combustor exit are nonuniform in the near-platform region as a result of cooling methods used for the combustor liner. These cooling methods include injection through film-cooling holes and injection through a slot that connects the combustor and turbine. This paper presents thermal and flow field measurements in the turbine vane passage for a combustor exit flow representative of what occurs in a gas turbine engine. The experiments were performed in a large-scale wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…"Inlet profile generators" are then used to approximate the combustor exit flow supplied to the turbine rig. State-of-the-art work along these lines include, most recently, the work of Colban and co-workers [3,4], Barringer and co-workers [5,6], Povey and Qureshi [7,8], and Simone et al [9]. These past approaches have led to an improved understanding of the sensitivity of the turbine to the various inflow parameters separately, e.g., OTDF level.…”
Section: Introductionmentioning
confidence: 95%
“…"Inlet profile generators" are then used to approximate the combustor exit flow supplied to the turbine rig. State-of-the-art work along these lines include, most recently, the work of Colban and co-workers [3,4], Barringer and co-workers [5,6], Povey and Qureshi [7,8], and Simone et al [9]. These past approaches have led to an improved understanding of the sensitivity of the turbine to the various inflow parameters separately, e.g., OTDF level.…”
Section: Introductionmentioning
confidence: 95%
“…One of the key findings was that the endwall adiabatic effectiveness distributions showed extreme variations across the vane gap with much of the coolant being swept across the endwall toward the suction side corner. Granser and Schulenberg [18], Colban et al [15], and Zhang and Moon [19] all reported similar adiabatic effectiveness results in that higher values occurred near the suction side of the vane relative to the pressure side. Based on their measurements, Roy et al [20], however, indicated that the coolant migrated toward the pressure side of the vane.…”
Section: Endwall Cooling Studiesmentioning
confidence: 56%
“…For this latter case, the rotation of the passage vortex was predicted to be counter-clockwise since the total pressure was lower towards the midspan. The experimentally measured secondary flows by Colban et al [15] in Fig. 3b shows what one might expect for an actual turbine where the upstream boundary layer is film-cooled in the combustor section and there is a backward facing slot flow at the combustor-turbine interface.…”
Section: Relevant Factors For Endwall Flowfield Developmentmentioning
confidence: 79%
See 2 more Smart Citations